2021
DOI: 10.1111/mmi.14806
|View full text |Cite
|
Sign up to set email alerts
|

The Sur7 cytoplasmic C terminus regulates morphogenesis and stress responses in Candida albicans

Abstract: The fungal pathogen Candida albicans has a complex relationship with human hosts. Under many conditions, it grows as a harmless commensal organism on the skin and GI tract mucosa (Kumamoto et al., 2020;Romo & Kumamoto, 2020). However, overgrowth of C. albicans due to conditions such as biofilm formation on medical devices or changes in the microbiome caused by antibacterial antibiotics can develop into lethal invasive infections in a wide range of different tissues (Kullberg & Arendrup, 2015;Noble et al., 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…STED microscopy confirmed that expression of Sur7 lacking the C‐terminus could not prevent the formation of tubes in the 5xΔ mutant (Fig 4D). These results are consistent with recent findings in C. albicans , which assigned a key function in regulating morphogenesis and stress responses to the Sur7 C‐terminus (Lanze et al , 2021). Importantly, despite its role in sculpting membranes, the Sur7 C‐terminus was not required for recruitment to MCC/eisosomes in WT cells and was still able to assemble into elongated strands in 5xΔ cells (Fig 4E).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…STED microscopy confirmed that expression of Sur7 lacking the C‐terminus could not prevent the formation of tubes in the 5xΔ mutant (Fig 4D). These results are consistent with recent findings in C. albicans , which assigned a key function in regulating morphogenesis and stress responses to the Sur7 C‐terminus (Lanze et al , 2021). Importantly, despite its role in sculpting membranes, the Sur7 C‐terminus was not required for recruitment to MCC/eisosomes in WT cells and was still able to assemble into elongated strands in 5xΔ cells (Fig 4E).…”
Section: Resultssupporting
confidence: 93%
“…The C‐terminal tails of claudins are known to be important sites of interaction with partner proteins and thereby promote tight junction formation in mammalian cells (Lal‐Nag & Morin, 2009). Similarly, the C‐terminal region of Sur7 has been shown to play a key functional role in C. albicans morphogenesis under various stress conditions (Lanze et al , 2021). Sur7 has been proposed to interact with the yeast cell wall through its extracellular domains (Young et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We further confirmed these results by STED microscopy where expression of Sur7 lacking the C-terminus could not prevent formation of tubes in the 5xΔ mutant (Fig 4D). These results are consistent with recent findings in C. albicans , which assigned a key function in regulating morphogenesis and stress responses to the Sur7 C-terminus (Lanze et al , 2021). Importantly, despite its role in sculpting membranes, the Sur7 C-terminus was not required for recruitment to MCC/eisosomes or for strand formation per se (STED, Fig 4E).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the C-terminal tails of tetraspanners are known to be important sites of interaction with partner proteins and thereby promote the biological functions of claudins (Lal-Nag & Morin, 2009). Similarly, the C-terminal region of Sur7 has been shown to play a key functional role in C. albicans morphogenesis under various stress conditions (Lanze et al , 2021). Further experiments will be required to identify the relevant protein and/or lipid interaction partners of the C-terminal segment that mediate its function in regulating membrane topography.…”
Section: Discussionmentioning
confidence: 99%
“…While disruptions of the MCC microdomain rarely lead to a growth-related phenotype in laboratory strains of S. cerevisiae , they are detrimental to morphogenesis and invasive growth of C. albicans ( 89 91 ). Our study adds to the growing body of data indicating that the MCC/eisosome is a viable target in the treatment of fungal infections ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 70%